KEWAJIBAN PEMBUATAN AKTA PEMBERIAN HAK TANGGUNGAN(APHT) SEGERA SETELAH DITETAPKAN SURAT KUASA MEMBEBANKAN HAK TANGGUNGAN (SKMHT) - Teguh Brawijaya, Enjang; Agung Ariani, I Gst. Ayu (Kertha Semaya : Journal Ilmu Hukum; Vol. 03, No. 01, Januari 2015)
Assessment of obligations deed granting a security interest (APHT) immediatelyset upon a power of attorney to charge a security interest (SKMHT) in the creditagreement on banking institutions. Basic settings are in the Law Number. 4 of 1996 onthe rights of dependents (UUHT).To obtain the data and the research literature juridical normative legalresearch, ie research that is based on the legal material and legal analysis.The results showed that the basic settings deed granting a security interest(APHT) immediately set upon a power of attorney to charge a security interest(SKMHT) and the reasons why it should APHT. Basic settings are set immediatelyafter the making of APHT SKMHT is in article 15, paragraph 5 UUHT. In theaforementioned article describes a security interest in the land and objects relating toland and limits of validity SKMHT given some sort of credit to guarantee certain. So,why should APHT? because it is the object of the right of dependents is the land so thatthe land certificate written in charged of mortgage, the debtor's nominal debt is writtenin the certificate.
Keywords: APHT, SKMHT